Linkae Analysis of Textile Finished Products, Pharmaceutical Products, and Health Sectors from the Perspective of Organizational Economics (Journal of research in medical and health sciences, 2025)
Based on the input-output analysis theory from the perspective of organizational economics, this study utilizes direct consumption coefficient matrices, total consumption coefficient matrices, and the Leontief inverse matrix to analyze the economic linkages among the textile finished products, pharmaceutical products, and health sectors. The results indicate that the pharmaceutical products sector exhibits significant "core-driven" and self-reinforcing characteristics, forming a deeply symbiotic relationship with the health sector. In contrast, the textile finished products sector demonstrates a "marginal supporting" role with relatively weak linkages. The study proposes that promoting the transformation of the textile sector into high-value-added fields such as medical textiles can foster synergistic development among the three sectors, providing a basis for optimizing industrial policies and enhancing supply chain resilience.
Keywords: Input-output analysis; Textile finished products; Pharmaceutical products; Health sector